Communication missteps during COVID‐19 hurt those already most at risk. (19th July 2020) - Clark‐Ginsberg, Aaron; Petrun Sayers, Elizabeth L.
Abstract: Emergency risk communication is a crucial part responding to crises. Right now, vulnerable groups are experiencing disproportionately negative outcomes from communication missteps surrounding COVID‐19. In this commentary, we describe the missteps and outline strategies that response organizations can take to improve communication for vulnerable groups.